2020
DOI: 10.1051/0004-6361/201936961
|View full text |Cite
|
Sign up to set email alerts
|

Searching for molecular gas inflows and outflows in the nuclear regions of five Seyfert galaxies

Abstract: Active galactic nucleus (AGN) driven outflows are believed to play an important role in regulating the growth of galaxies, mostly via negative feedback. However, their effects on their hosts are far from clear, especially for low- and moderate-luminosity Seyferts. To investigate this issue, we obtained cold molecular gas observations, traced by the CO(2-1) transition, using the NOEMA interferometer of five nearby (distances between 19 and 58 Mpc) Seyfert galaxies. The resolution of ∼0.3–0.8 (∼30–100 pc) and fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 149 publications
2
22
1
Order By: Relevance
“…This is the first time the frequency of central molecular outflows in high resolution and high sensitivity data has been robustly estimated as frequency determination in molecular gas are rare, and sample sizes are often small. For example, Domínguez-Fernández et al (2020) analyzed the CO (2-1) emission in five nearby Seyfert galaxies and find two of their targets being likely to host an outflow. Wylezalek et al (2020) used the MaNGA sample of galaxies at mean redshift of z ∼ 0.03 to determine the outflow frequency in galaxies.…”
Section: Literature Outflow Frequenciesmentioning
confidence: 99%
“…This is the first time the frequency of central molecular outflows in high resolution and high sensitivity data has been robustly estimated as frequency determination in molecular gas are rare, and sample sizes are often small. For example, Domínguez-Fernández et al (2020) analyzed the CO (2-1) emission in five nearby Seyfert galaxies and find two of their targets being likely to host an outflow. Wylezalek et al (2020) used the MaNGA sample of galaxies at mean redshift of z ∼ 0.03 to determine the outflow frequency in galaxies.…”
Section: Literature Outflow Frequenciesmentioning
confidence: 99%
“…The NOEMA observations and data reduction for the galaxies in our sample (see Table 3) are described in detail in Domínguez-Fernández et al (2020). The majority of the ALMA observations used in this work are either from our own programs or are taken from the ALMA archive.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…3). We used the NOEMA CO(2-1) maps generated for detections >3σ from Domínguez-Fernández et al (2020). Figure 1 shows the maps of the integrated CO(2-1) line emission for the galaxies analyzed in this work (see Sect.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Cold molecular outflows in the nearby universe have been studied in low-to-intermediate luminosity AGN (i.e., Seyfert galaxies with L IR < 10 12 L ) and ultra-luminous infrared galaxies (ULIRGs), mainly, but not only, using hydroxyl (OH) and carbon monoxide (CO) transitions (see Veilleux et al 2020 for a recent review). Focusing on CO-based studies, it has been found that the two types of objects show very different outflow properties, going from maximum velocities of ∼100-200 km s −1 and outflow rates of 10 M yr −1 in Seyfert galaxies (e.g., Alonso-Herrero et al 2019;Domínguez-Fernández et al 2020;García-Bernete et al 2021), to >300 km s −1 and hundreds of M yr −1 in ULIRGs (e.g., Cicone et al 2014;Pereira-Santaella et al 2018;Fluetsch et al 2019Fluetsch et al , 2021Herrera-Camus et al 2020). It is noteworthy that jetted Seyfert galaxies like NGC 1068 and IC 5063 (García-Burillo et al 2014Morganti et al 2015) show much higher outflow velocities and masses than those without, indicating the strong influence that jets might have in launching/accelerating molecular outflows (Wylezalek & Morganti 2018;Jarvis et al 2019).…”
Section: Introductionmentioning
confidence: 99%